Cost-Effectiveness Analysis of Tyrosine Kinase Inhibitors in Gastrointestinal Stromal Tumor: A Systematic Review - Feng, Mingyang; Yang, Yang; Liao, Weiting; Li, Qiu (Frontiers in Public Health, 2022)
Background: The introduction of tyrosine kinase inhibitor (TKI) therapy has dramatically improved the clinical effectiveness of patients with locally advanced and/or metastatic gastrointestinal stromal tumors (GIST), and this systematic review was conducted aiming at the cost-effectiveness analysis of TKIs in GIST. Methods: A thorough literature search of online databases was performed, using appropriate terms such as “gastrointestinal stromal tumor or GIST,” “cost-effectiveness,” and “economic evaluation.” Data extraction was conducted independently by two authors, and completeness of reporting and quality of the evaluation were assessed. The systematic review was conducted following the PRISMA statement. Results: Published between 2005 and 2020, 15 articles were incorporated into the systematic review. For advanced GIST, imatinib followed by sunitinib was considered cost-effective, and regorafenib was cost-effective compared with imatinib re-challenge therapy in the third-line treatment. For resectable GIST, 3-year adjuvant imatinib therapy represented a cost-effective treatment option. The precision medicine-assisted imatinib treatment was cost-effective compared with empirical treatment. Conclusion: Although identified studies varied in predicted costs and quality-adjusted life years, there was general agreement in study conclusions. More cost-effectiveness analysis should be conducted regarding more TKIs that have been approved for the treatment of GIST. Systematic Review Registration:https://www.crd.york.ac.uk/, PROSPERO: CRD42021225253.